Hubungan Tingkat Aktivitas Fisik Dan Stres Terhadap Siklus Menstruasi Pada Atlet Karate Putri Di Universitas Negeri Surabaya - Citra Najwa Fadila; Noortje Anita Kumaat (STIKes Ibnu Sina Ajibarang, 2024)
The problem that is often experienced by female athletes is menstrual disorders. High levels of physical activity in athletes resulting from intensive training and stress regarding targets that must be achieved can be factors causing menstrual cycle disorders. This research aimed to determine the relationship between levels of physical activity and stress on the menstrual cycle of female karate athletes at Surabaya State University. The descriptive quantitative method was chosen for research on female karate athletes at Surabaya State University with a population of 48 athletes. With purposive sampling technique, 37 samples were obtained. The results of the univariate analysis showed that athletes' physical activity was dominated by the heavy category, namely 29 people (78.4%) and 8 people (21.6%) in the moderate category. The stress level was dominated by the moderate category, namely 28 people (75.7%), the light category was 6 people (16.2%), and the heavy category was 3 people (8.1%). Most of the athletes experienced polymenorrhoea, 15 people (40.5%), 9 people (24.3%) had oligomenorrhea, and 13 people (35.1%) had normal menstrual cycles. The results of bivariate analysis using the chi square test obtained p < 0.05 for both independent variables, which means there is a relationship between the level of physical activity and stress on the menstrual cycle of female karate athletes at Surabaya State University. So it is recommended to pay attention to the duration of physical activity and carry out stress management.